N-heterocyclic carbenes : effective tools for organometallic synthesis - Nolan, Steven P. (Weinheim, Germany : Wiley-VCH, 2014)
"This comprehensive reference and handbook covers in depth all major aspects of the use of N-heterocyclic carbene-complexes in organic synthesis: from the theoretical background to characterization, and from cross-coupling reactions to olefin metathesis. Edited by a leader and experienced scientist in the field of homogeneous catalysis and use of NHCs, this is an essential tool for every academic and industrial synthetic chemist." --
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed Aug. 13, 2014).
Keywords: Carbenes (Methylene compounds); Organometallic compounds -- Synthesis; Carbenes (Methylene compounds); Organometallic compounds -- Synthesis; Electronic books